Do Neurobiological Understandings of Smoking Influence Quitting Self-Efficacy or Treatment Intentions?. Issue 7 (22nd June 2017) - Morphett, Kylie; Carter, Adrian; Hall, Wayne; Lucke, Jayne; Partridge, Brad; Gartner, Coral
Abstract: Introduction: Addiction is increasingly defined as a "brain disease" caused by changes to neurochemistry. While nicotine addiction has historically been excluded in the brain disease model of addiction (BDMA), it is beginning to be labeled a chronic brain disease. We investigated whether Australian smokers endorse brain-based explanations of smoking, and whether these beliefs are associated with quitting self-efficacy or treatment intentions. Method: Cross-sectional study of Australian smokers ( N = 1538) who completed a survey measuring their agreement with statements on the brain's role in smoking. Logistic regressions tested associations between these items and socio-demographic variables, quitting self-efficacy and intention to use cessation medications. Results: The majority (57.9%) agreed that smoking changed brain chemistry and 34.4% agreed that smoking was a brain disease. Younger participants and those with more education were more likely to endorse brain-based understandings of smoking. Participants who agreed smoking changed brain chemistry were more likely to report an intention to use cessation medicines (OR 1.5, 95% CI = 1.0–2.2) as were those who agreed that smoking was a brain disease (OR 1.5, 95% CI = 1.1–2.1). Self-efficacy did not differ between those who agreed and disagreed that smoking changed brain chemistry. However, those who agreed that smoking was a brain disease had higher self-efficacy than those who disagreed (OR 1.7, 95% CI = 1.3–2.3). Conclusion: A neurobiological view of smoking does not dominate public understandings of smoking in Australia. Endorsement of neurobiological explanations of smoking were associated with increased intention to use cessation aids, but were not associated with reduced self-efficacy. Implications: Explaining tobacco dependence in neurobiological terms is unlikely to induce feelings of fatalism in relation to smoking cessation. Those who endorse biomedical explanations of smoking may be more open to using cessation pharmacotherapies. Describing smoking in terms of alterations in brain chemistry may be more acceptable to smokers than labeling smoking a "brain disease" or "brain disorder."